An examination of therapeutic synergy: a comprehensive meta-analysis comparing the efficacy of TAS-102 and FOLFOX as a combination therapy for colon cancer - Hasan, Amit (Brac University, 2024)
This project report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2024.